Pengaruh E-biling Dan E-filing Terhadap Kepatuhan Wajib Pajak Orang Pribadi Di KPP Pratama Bandung Tegallega - Mulyana, Asep; Sihombing, Jojor Trianita; Sutrisna, Wawan Asad (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2025)
This research aims to obtain evidence of the influence of e-billing and e-filing on individual taxpayer compliance at KPP Pratama Bandung Tegallega. This research was conducted on individual taxpayers registered at KPP Pratama Bandung Teggalega. The population in this research is all individual taxpayers at KPP Pratama Bandung Tegallega 2024. With a sample size of 100 respondents, the method in this research uses quantitative methods. The questionnaire uses a closed questionnaire. The questionnaire data is first tested for validity and reliability, then the assumptions of the classical test are tested and the examiner finally tests the hypothesis. The results of this study show that e-billing has no significant effect on individual taxpayer compliance, while e-filing has a significant effect on individual taxpayer compliance